Infantile myofibromathosis of the maxilla - Ihan Hren, Nataša (Radiology and oncology (Ljubljana), 2002)
Background. Infantile myofibromatosis is a rare benign tumour in children. Itscharacteristic symptoms are firm masses in soft tissues, bones and visceralorgans, and its common locations are head and neck. Three forms are well known: solitary, multicentric and visceral myofibromatosis. All have excellent prognosis, except the last one that may be lethal. Spontaneous regression can occur. Case report. We present an unusual case of infantile myofibromatosis of the maxilla in an adolescent. Conclusions. The infantile myofibromatosis should be managed with special caution because of the differential-diagnostic similarity with fibrosarcoma, leomyosarcoma, and histiocytosis.
Keywords: Child; Diagnosis; maksila; Maksilarne novotvorbe; Maxillary neoplasms; Miofibromatoza; Myofibromatosis; novotvorbe; otroci; Otrok; rak (medicina); Surgery; tumor